A philosophical investigation of the transition from integrated marketing communications to metamodern meaning co-creation - Panigyrakis, George G.; Zarkada, Anna K. (My University, 2014)
This article contributes to the recent problematisation of the co-evolution of philosophy and marketing thought as we experience a transition from the deification of greed, individualism and hedonic consumption seen during the postmodern period of the twentieth century to the brutal class restructuring and shattering of a number of illusions of metamodernity at the beginning of the twenty-first century. It examines the philosophical foundations of advertising and communication and demonstrates the ways in which current technological and socio-political advances are rendering traditional approaches obsolete. As marketing is now recognised to be the mechanism par excellence for value co-production, so advertising – and communication in general – are but mechanisms of meaning co-production through a dialogue between the disillusioned but empowered consumer and the brand and corporation on solidarity, responsibility, morality, dignity and the sense of belonging in a community. It is hereby argued that values are far more relevant to contemporary consumers than the pursuit of an idealised lifestyle based on celluloid images of the imaginary Joneses, and thus it is advocated that discipline-wide changes need to be made.
Keywords: Philosophy; Metamodernity; IMC; Advertising; Service-dominant logic